2004
DOI: 10.1097/00004770-200411000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Ozonated Water on Bacteria Invading Dentinal Tubules

Abstract: Ozone is known to act as a strong antimicrobial agent against bacteria, fungi, and viruses. In the present study, we examined the effect of ozonated water against Enterococcus faecalis and Streptcoccus mutans infections in vitro in bovine dentin. After irrigation with ozonated water, the viability of E. faecalis and S. mutans invading dentinal tubules significantly decreased. Notably, when the specimen was irrigated with sonication, ozonated water had nearly the same antimicrobial activity as 2.5% sodium hypoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
216
6
36

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(269 citation statements)
references
References 20 publications
11
216
6
36
Order By: Relevance
“…Ozone is known to act as a strong antimicrobial agent 78 and has been shown to effectively disinfect bovine dentinal tubules in vivo. 79 These developments in the field of root canal disinfection provide encouraging results for future development of novel irrigation materials and techniques that can be used instead of or as adjunct to the conventional materials currently in use.…”
Section: Future Development In Root Canal Irrigationmentioning
confidence: 99%
“…Ozone is known to act as a strong antimicrobial agent 78 and has been shown to effectively disinfect bovine dentinal tubules in vivo. 79 These developments in the field of root canal disinfection provide encouraging results for future development of novel irrigation materials and techniques that can be used instead of or as adjunct to the conventional materials currently in use.…”
Section: Future Development In Root Canal Irrigationmentioning
confidence: 99%
“…Nagayoshi et al 23 found that ozonated water was effective against Gram-positive and Gramnegative oral microorganisms and oral Candida albicans in pure culture. Ozonated water also had strong bactericidal activity against the bacteria in biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Shur et al (2003) chlorhexidine-impregnated and iodoform-containing gutta-percha points have shown little inhibitory action against E. faecalis. In Nagayoshi et al (2004), ozonated water has been shown to have the same antimicrobial efficacy as 2.5% sodium Hypochlorite. In , the antimicrobial activity against E. faecalis of various sealers has also been studied.…”
Section: Steps That Can Be Considered For the Elimination And Preventmentioning
confidence: 99%